Pengaruh Ukuran Perusahaan, Leverage dan Profitabilitas terhadap Environmental Disclosure (Studi Empiris pada Perusahaan Manufaktur Subsektor Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Dian Kartiko; Sofyan Halim (JUDICIOUS, 2022)
This research was conducted to test the Effect of Company Size, Leverage and Profitability on Environmental Disclosure. The independent variables used in this study were Company Size, Leverage and Profitability. While the dependent variable used in this study is Environmental Disclosure. This study used a chemical subsector manufacturing company listed on the Indonesia Stock Exchange in 2017-2021. The sample obtained in this study was 35 samples from 7 companies for 5 years. The sample determination technique uses the purposive sampling method. Hypothesis testing in this study used Multiple Linear Regression Analysis with SPSS 23 program and significance level of 5%. The results of the test show that, Company Size has a significant positive effect on Environmental Disclosure, Leverage has a significant positive effect on Environmental Disclosure, and Profitability has a significant positive effect on Environmental Disclosure. There are limitations of the research that has been carried out. This study only used one subsector of manufacturing companies, namely Chemical Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange with relatively few observations, thus allowing the practice of disclosure of the observed company's environment to not describe the actual conditions, it is illustrated from the test on the Adjusted R square getting a result of 38.8%, meaning that there are other independent variable factors outside the model in this study thus producing more adequate research.